PERSEPSI MASYARAKAT TERHADAP KEBERADAAN HUTAN DISEKITAR KEBUN KELAPA SAWIT DESA LEMBAH HIJAU 1 KECAMATAN NANGA TAYAP KABUPATEN KETAPANG - Sariman, Wahyu; Thamrin, Edy; Idham, M (Universitas Tanjungpura, 2017)
Indonesia has ample natural resources such as various species of plants, timber and non timber, which can be utilized for the prosperity of people. Forest cover where the plants grow is also important to absorb carbon dioxide and to perform photosynthesis to produce oxygen. Ketapang regency is one of the areas in West Kalimantan which has good potential forest resources, for instance in Nanga Tayap District Lembah Hijau 1 Village. Before the existence of oil palm plantations in Lembah Hijau 1 Village, the condition of its forest was quite good, but as the time goes on the forest becomes alarming, this is due to the expansion of palm plantation while people’s needs of wood for construction becomes higher. Success in protecting forest counts on the participation of surrounding communities. This research aimed to find out how was people’s perception of the existence of forest around the palm oil plantation and to analyze the correlation between people’s perception of the existence of forest around the palm oil plantation and the level of age, education, income, knowledge, and cosmopolitan. The result shows that the perception tends to be positive on the existence of forest around the palm oil plantation. And the analysis shows that the level of age, education, and income do not have a correlation with people’s perception of the existence of forest around the palm oil plantation. But the level of knowledge and cosmopolitan have a correlation with people’s perception of the existence of forest around the palm oil plantation.Keywords: communities around the forest, palm oil plantation, perception